Calcium silicate to reduce heavy metal toxicity in eucalyptus seedlings - Accioly, Adriana Maria de Aguiar; Soares, Cláudio Roberto Fonsêca Sousa; Siqueira, José Oswaldo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this study was to evaluate the effect of calcium silicate to reduce heavy metal toxicity in Eucalyptus camaldulensis seedlings. Five doses of calcium silicate (0, 1.6, 3.2, 4.8, and 6.4 g kg-1) were used in soils with increasing levels of contamination. The experiment was carried out in pots with 1.5 kg of soil, with one plant each, in a 4x5 factorial array (four levels of contamination x five silicate doses). Calcium silicate minimized heavy metal toxicity to E. camaldulensis, delayed the onset of toxicity symptoms, and decreased zinc and cadmium shoot concentrations. However, calcium silicate did not completely overcome the depressive effect upon plant growth in soils with high metal concentrations. Calcium silicate effects increased with increasing doses and were more evident in highly contaminated soils. The beneficial effects of calcium silicate on metal toxicity were highly related to the decrease in zinc translocation to the eucalyptus shoots.
Keywords: Eucalyptus camaldulensis; cadmium; phytostabilization; phytotoxicity; soil pollution; zinc